Epidemiological profile of patients hospitalized for malignant breast neoplasm in males in the state of Minas Gerais, Brazil, from 2008 to 2017 - Karoline Soares Fonseca, Maria; Jorge Silveira, Brisa; Braga Almeida, Mariana; Jorge Silveira, Breno; Andrade de Prince, Karina (Revista Unimontes Científica, 2020)
Objective: To characterize the hospitalization and death rates due to malignant breast neoplasm in men, in Minas Gerais, between 2008 and 2017, through data collected from the Hospital Information System of the Unified Health System (SIH/SUS). Such knowledge can enrich the epidemiological data and strengthen prevention and diagnostic actions. Methodology: This is a cross-sectional, retrospective, descriptive, and quantitative study. Data related to hospitalizations and deaths due to malignant neoplasm of breast in men, in the state of Minas Gerais, Brazil, between 2008 and 2017, were obtained from the Hospital Information System of the Unified Health System. The variables used were: number of hospitalizations according to age, race, elective or emergency care, public or private facilities, region of the state, and number of deaths. Results: A total of 696 hospitalization cases were identified, with predominance in the Center (28.88%) and Southeast (25.43%) regions of Brazil. Regarding the institution of attendance, 66.96% occurred in private facilities. About race, 38.36% declared themselves to be brown. The number of deaths was 42, corresponding to 6.03% of the hospitalizations. The highest mortality rate (10.22%) was observed in patients from 70 and 79 years old. Conclusion: The highest number of admissions, deaths, and mortality rates was observed around 60 years old. Most of the hospitalizations and the highest medical expenses occurred in private institutions. The Central and Southeastern regions of Brazil presented the highest number of admissions, which might be explained by the higher concentration of reference centers for cancer treatment in these areas.